Improved statistical machine translation for resource-poor languages using related resource-rich languages - Nakov, P. (2013)
EMNLP 2009 - Proceedings of the 2009 Conference on Empirical Methods in Natural Language Processing: A Meeting of SIGDAT, a Special Interest Group of ACL, Held in Conjunction with ACL-IJCNLP 2009